Influence of biotin intervention on glycemic control and lipid profile in patients with type 2 diabetes mellitus: A systematic review and meta-analysis - Zhang, Yujia; Ding, Yiwang; Fan, Yawen; Xu, Yenan; Lu, Yuting; Zhai, Lingzi; Wang, Ling (Frontiers in Nutrition, 2022)
Background: Biotin is a water-soluble vitamin acting as a covalently bound coenzyme in regulating energy production. Previous studies have reported that biotin supplementation may influence blood glucose and lipid level in patients with type 2 diabetes mellitus (T2DM). Methods: We searched Pubmed, Embase, and Cochrane library databases up to 8th August 2022 for studies examining the effects of biotin supplementation in T2DM patients. Pooled effects were measured by weighted mean differences (WMDs) with 95% confidence intervals (CI) using random effects models. Inter-study heterogeneity was assessed and quantified. Results: A total of five random controlled trials (RCT), involving 445 participants were included. It was suggested that biotin supplementation for 28 to 90 days significantly decreased the level of fasting blood glucose (FBG) (MD: -1.21 mmol/L, 95% CI: -2.73 to 0.31), total cholesterol (TC) (MD: -0.22 mmol/L, 95% CI: -0.25 to -0.19) and triglycerides (TG) (MD: -0.59 mmol/L, 95% CI: -1.21 to 0.03). No significant beneficial effects were observed on insulin (MD: 1.88 pmol/L 95% CI: -13.44 to 17.21). Evidence for the impact of biotin supplementation on the levels of glycated hemoglobin (HbA1c), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and very low-density lipoprotein cholesterol (VLDL-C) was limited to draw conclusion. Conclusion: Biotin supplementation may decrease FBG, TC and TG levels. However, its influence on insulin is not significant and further studies on the effects of biotin on HbA1c, LDL-C, HDL-C and VLDL-C are expected.